OPTIMIZATION OF CYCLE TIME AND REDUCTION OF TAILED ON TOP DEFECTS IN BOTTLE CAPS USING TAGUCHI METHOD - Nanda Pratiwi; Diana Ross Arief; Herry Suseno; Adam Dio Zaidan Dhuha (Politek ATK Yogyakarta Press, 2024)
The purpose of this study is to determine the optimal cycle time and reduced defects of tailed on top in bottle cap products. Defects of tailed on top are defects in the form of residual plastic material that hardens at the top of the bottle cap where the material enters when injected. The method used in this final project was to conduct an experimental design using orthogonal array by varying the influential parameters and ANOVA calculation. Furthermore, this paper also calculated the Taguchi method by using Minitab 18 software. The result show that the optimal condition is combination parameters cooling time of 8 seconds, injection time of 2.10 seconds and hot runner nozzle temperature of 230oC produces a cycle time value of 17,11 seconds and percentage defects 1,56%.